Thermal Stability and Kinetics of Thermal Decomposition of Statistical Copolymers of N-Vinylpyrrolidone and Alkyl Methacrylates Synthesized via RAFT Polymerization - Theodoros Gikarakis; Ioannis Pappas; Pothiti Arvanitaki; Ekaterini Pantazi; Eleftheria Mitsoni; Nikoletta Roka; Marinos Pitsikalis (Journal of Chemistry)
The thermal stability and the kinetics of thermal decomposition of statistical copolymers of N-vinylpyrrolidone (NVP) with the alkyl methacrylates, hexyl methacrylate (HMA) and stearyl methacrylate (SMA), were studied by Thermogravimetric Analysis (TGA) and Differential Thermogravimetry (DTG). Statistical copolymers of different compositions were studied, and their thermal decomposition behavior was compared to the corresponding homopolymers. The activation energies of the thermal decomposition were calculated using the Ozawa-Flynn-Wall, the Kissinger, and the Kissinger-Akahira-Sunose methodologies. The effects of the nature of the methacrylate monomer, the copolymer composition, and the rate of heating are discussed.